Biomethanation of sewage wastewater using ultrasonic membrane anaerobic system (UMAS) - Alzubeer, Mohammed Ahmed Mohammed (2019)
Sewage wastewater is hard wastewater that contains a high amount of chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solids (TSS) and volatile suspended solids (VSS). These vital parameters should be treated first before it is discharged into any waterways. There are many treatment methods implied until this decade with the traditional approach. Pond system is the most implied method due to its low cost. The sewage wastewater was treating to produce methane gas by using membrane anaerobic digestion method. But there will be membrane fouling problem caused by high amounts of total solids carried by the wastewater. Therefore the operating cost of the treatment plant it will be very high. Thus, Ultrasonic Membrane Anaerobic System (UMAS) is used as an alternative method to overcome this problem. The sewage wastewater was collected from Kuantan Water Indah and acclimatizing for 5 days before running the reactor, The row wastewater parameter was recorded, COD was 164.67 mg/L, and BOD was 17.4 mg/L, and TSS was 31 mg/L, and VSS was 6mg/L, the pH, pressure and temperature was kept being constant during the experiment within the values of 6.5 to 7.5, 2 to 3 bar and 35 to 46 ºC respectively. The performance of Ultrasonic Membrane Anaerobic System UMAS is evaluated on the ability of (UMAS) to treat these parameters. The UMAS must be operated daily for 5 hours operation per day. The experiment is done when the UMAS is achieving a steady state. The steady state is achieved on day 5. The performance of UMAS showed high COD removal efficiency with 97.4%. and BOD removal efficiency with 92%, TSS removal efficiency 97% and VSS removal efficiency 99% and the methane gas composition obtained was about 79%. Based on the result obtained after ten days of the experiment shows that UMAS can treat strength and low wastewater, with no membrane fouling problem and produce methane gas from sewage wastewater. Moreover, further works are required to provide more in-depth understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the field of the wastewater treatment plant.